Modeling and control of the hydraulic actuator in a ladle furnace (2022)
The dynamic behavior of the hydraulic actuator in a system for regulating the electrode's position is crucial for the operation of a Ladle Furnace. This work aims to identify, model, and control the hydraulic actuator in the Ladle Furnace of ACINOX Las Tunas. For identifying the system, input signals of Pseudo-Random Binary type and black box models were used. As a result, three models were obtained, two reflecting the process's asymmetric behavior according to the upward or downward movement. The third model approximates the process dynamic behavior around the operating point and includes the uncertainty caused by the weight variation during the electrode wear. The models obtained, with a fit greater than 85%, allow a better understanding of the study case behavior. In addition, these allowed the evaluation of the electrode's weight variation and tuning of several controllers. The optimal one was a novel non-linear PI controller of guaranteed robustness. In future works, the use of a non-linear function could be evaluated to compensate for the asymmetric behavior of the process.